Anthropogenic 129I in the sediment cores in the East China sea: Sources and transport pathways. (February 2019) - Zhao, Xue; Hou, Xiaolin; Du, Jinzhou; Fan, Yukun
Abstract: With the increased numbers of nuclear power plants constructed along the east coast of China, it is important to know radioactive sources and transport pathways between land and sea, in order to better understand the impact of these nuclear facilities to the marine environment. Two sediment cores collected from the East China Sea dated to 1959–2010 were analyzed for long-lived radioactive 129 I and stable 127 I. It was observed that 129 I levels ( 129 I/ 127 I ratio of (15.0–75.0) × 10 −12 ) were significantly increased compared to the pre-nuclear value ( 129 I/ 127 I = 1.5 × 10 −12 ). Some 129 I peaks were observed in layers of 1959, 1966, 1971 and 1976 (1977), corresponding to the atmospheric nuclear weapon tests at Pacific Proving Grounds and Lop Nor. The high values of 129 I after the late 1970s are attributed to the releases from the European reprocessing plants. In addition to ocean current transport, the atmospheric dispersion through the interaction of the Westerlies with East Asia monsoon is the important pathway of large-scale transport of pollutants from high latitude West Europe to middle latitude East Asia. Riverine input is the main transport pathway of radioactive pollutants released from Lop Nor to the East China Sea through the atmospheric dispersion, deposition and runoff processes. Graphical abstract: Highlights: Radioactive pollutants deposited on land was transported and trapped in the East China Sea. 129 I profiles of sediment core in the East China Sea provide the historic records of human nuclear activities. Westerlies and East Asian Winter Monsoon brings gaseous pollutant from West Europe to the ECS. Riverine input undertakes the transport of radionuclides from Lop Nor to the ECS. Abstract : The sources and transport pathway of anthropogenic 129 I in the ECS was investigated to estimate the impact of the human nuclear activities to the marine ecosystem in the east China sea and to improve the understanding of pollutant dispersion.